2013
DOI: 10.1016/s0325-7541(13)70018-x
|View full text |Cite
|
Sign up to set email alerts
|

First clinical isolates of Cronobacter spp. (Enterobacter sakazakii) in Argentina: Characterization and subtyping by pulsed-field gel electrophoresis

Abstract: Cronobacter species are opportunistic pathogens associated with severe infections in neonates and immunocompromised infants. From January 2009 through September 2010, two cases of neonatal infections associated with Cronobacter malonaticus and one case associated with Cronobacter sakazakii, two of them fatal, were reported in the same hospital. These are the first clinical isolates of Cronobacter spp. in Argentina. The objective of this work was to characterize and subtype clinical isolates of Cronobacter spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Initially, powdered infant formula was thought to be the major source of these pathogens since the product is not sterile, however, studies have shown that Cronobacter spp. are ubiquitous opportunistic pathogens (Pagotto and Farber 2009 ; Asato et al 2013 ; Craven et al 2010 ; Lehner et al 2010 ; Mozrová et al 2014 ; Mullane et al 2008 ). They have been isolated from different sources ranging from animal related food sources like powdered infant formula, follow up formula and plant related food sources like vegetables, herbs and spices (Joseph et al 2012 ; Althaus et al 2012 ; El-Sharoud et al 2009 ; Hochel et al 2012 ; Molloy et al 2009 ; O’Brien et al 2009 ; Schmid et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, powdered infant formula was thought to be the major source of these pathogens since the product is not sterile, however, studies have shown that Cronobacter spp. are ubiquitous opportunistic pathogens (Pagotto and Farber 2009 ; Asato et al 2013 ; Craven et al 2010 ; Lehner et al 2010 ; Mozrová et al 2014 ; Mullane et al 2008 ). They have been isolated from different sources ranging from animal related food sources like powdered infant formula, follow up formula and plant related food sources like vegetables, herbs and spices (Joseph et al 2012 ; Althaus et al 2012 ; El-Sharoud et al 2009 ; Hochel et al 2012 ; Molloy et al 2009 ; O’Brien et al 2009 ; Schmid et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed-field gel electrophoresis was used to evaluate the CSF isolates from both infants using standard techniques and digestion by Spe I and Xba I. 8 The pulsed-field gel electrophoresis banding profiles were distinct for each isolate. The isolate detected from the opened can of formula by the health department was not available for evaluation.…”
Section: Case Reportsmentioning
confidence: 99%
“…5 However, data on the performance of QFT-Plus in the pediatric age group remain limited, with most studies primarily having focused on test sensitivity. [5][6][7][8] This study aimed to determine the specificity of QFT-Plus assays in children and adolescents with suspected TB in a low TBburden setting.…”
mentioning
confidence: 99%
“…To have a specific PFGE protocol for subtyping Cronobacter species, an initial development and multicenter validation process (Brengi et al , 2012) was done at INEI-ANLIS, Argentina, working together with four other laboratories: CDC, United States; the National Microbiology Laboratory of Health Canada, Canada; the World Health Organization (WHO) Cronobacter Reference Laboratory, University College Dublin, Ireland; and the Institute for Food Safety and Hygiene, University of Zurich, Switzerland. This protocol was useful to investigate the first episode of fatal cases of neonatal infections associated with Cronobacter malonaticus and C. sakazakii in the same hospital in Argentina that occurred from January 2009 through September 2010 (Asato et al , 2013). Also another fatal case associated with C. sakazakii occurred in Costa Rica was studied and it demonstrated that the same strain was isolated from the girl and the powdered infant formula that she had sampled at home.…”
Section: Strength Of the Networkmentioning
confidence: 99%